A New Model for Reimbursing Genome‐Based Cancer Care. (5th December 2013) - Ramsey, Scott D.; Sullivan, Sean D.
Abstract : Molecularly targeted medicine poses substantial challenges for incorporation into the existing U.S. health care system. It is argued here that performance‐based risk‐sharing arrangements may be a promising approach to address the competing needs of patients, clinicians, and payers.